BUDGET PLANNING STRATEGY SPENDING INCOME IN MADRASAS - Ma’ruf, Muh. Arif; Fauziyah, Helmiyatunnisa; Yusra, Agnes (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the Development of pesantren (Islamic Boarding Schools) internally. This study describes the strategy for preparing the madrasah expenditure budget plan in MAN 1 Bandung City. This strategy will be compared with the existing legal basis and how school leaders formulate a budget to improve the quality of education. This research method is a qualitative approach with descriptive methods. Descriptive research can only describe a situation but can also describe conditions in the stages of its Development. Sukmadinata stated & that; descriptive research is a method aimed at describing existing phenomena at present or in the past